Divergent Skull Morphology Supports Two Trophic Specializations in Otters (Lutrinae) - Timm-Davis, Lori L.; DeWitt, Thomas J.; Marshall, Christopher D. (PLOS ONE, 2015)
Variation in terrestrial mammalian skull morphology is known to constrain feeding performance, which in turn influences dietary habits and ultimately fitness. Among mustelids, otters have evolved two feeding specializations: underwater raptorial capture of prey (mouth-oriented) and capture of prey by hand (hand-oriented), both of which have likely associations with morphology and bite performance. However, feeding biomechanics and performance data for otters are sparse. The first goal of this study was to investigate the relationships between feeding morphology and bite performance among two mouth-oriented piscivores (Pteronura brasiliensis and Lontra canadensis) and two hand-oriented invertebrate specialists (Enhydra lutris and Aonyx cinerea). Since other vertebrate taxa that are mouth-oriented piscivores tend to possess longer skulls and mandibles, with jaws designed for increased velocity at the expense of biting capability, we hypothesized that mouth-oriented otters would also possess long, narrow skulls indicative of high velocity jaws. Conversely, hand-oriented otters were expected to possess short, blunt skulls with adaptations to increase bite force and crushing capability. Concomitant with these skull shapes we hypothesized that sea otters would possess a greater mandibular bluntness index, providing for a greater mechanical advantage compared to other otter species investigated. A second goal was to examine morphological variation at a finer scale by assessing variation in cranial morphology among three sea otter subspecies. Since diet varies among these subspecies, and their populations are isolated, we hypothesized that the magnitude of mandibular bluntness and concomitant mechanical advantage, as well as occlusal surface area would also vary within species according to their primary food source (fish versus hard invertebrates). Functional expectations were met for comparisons among and within species. Among species the phylogeny suggests a deeply rooted transition to alternative foraging types. Yet within foraging types alternative species were also strongly variable, suggesting either selective differences in the extent or nature of realized foraging mode, or an accumulation of non-adaptive changes during the long independent evolutionary history. At the finest scale, variation among subspecies indicates that trophic adaptation occurred rapidly, making it interesting that we happened to find both deeply and shallowly-rooted transformations associated with diet type in otter species and subspecies.